Rural resistance in South Africa : the Mpondo revolts after fifty years - Kepe, Thembela; Ntsebeza, Lungisile (Afrika-Studiecentrum Series, 2011)
Drawing on scholarship from multiple disciplines, this volume presents a fresh understanding of the Mpondo uprising in South Africa; focusing on its meanings and significance in relation to land, rural governance, politics and the agency of the marginalized.